PENGGUNAAN MODEL MAKE A MATCH DALAM PEMBELAJARAN PKN DI KELAS V SDN 07 SEBANDUT BENGKAYANG - Apuan, Apuan; Halidjah., Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrak The research problem is whether there is an increase in student learning outcomes in learning Citizenship Education using Make a match model in class V Public Elementary School 07 Sebadut Bengkayang Regency. Research aims to improve student learning outcomes through the use of Make a match model. The method used in this research is descriptive method in the form of Classroom Action Research, is collaborative. Data collection techniques used are the technique of direct observation and measurement by means of data collection is the Student Worksheet. Setting research with subject Teachers / Researchers and students of class V amounted to 21 students.The results of the three cycles obtained are: 1) The ability of teachers to plan the learning model Make a Match experienced an average increase of 0.59 with an average value of 3.23. 2) The ability of teachers to implement learning model Make a Match experienced an average increase of 0.46 with an average value of 3.07. 3) Student learning outcomes Make a Match model increased the increment of 5.83 with an average value of 65.18.Conclusion: the use of Make a match model in Civic Education learning can improve student learning outcomes. Suggestion: Teachers are expected to use Make a match model in improving student learning outcomes in the future. Keywords: Learning outcomes, Model Make a match, Citizenship Education.